On the making : the power of objects, the act of 'making' and their capacity for facilitating agency in the lives of women : an exegesis presented in partial fulfillment of the requirements for the degree of Masters in Fine Arts at Massey University, Wellington, New Zealand - McQuarrie, Caroline (Massey University, 2005)
No abstract
Keywords: Expression in art; Clothing in art; Women and art; Creativity